Spatial Dimensions of Trade Liberalization and Economic Convergence: Mexico 1985-2002 - Aroca, Patricio; Bosch, Mariano; Maloney, William F. (World Bank, Washington, DC, 2012)
This paper studies the spatial dimension of growth in Mexico over the past three decades. The literature on regional economic growth shows a decrease in regional dispersion from 1970 to 1985, and a sharp increase afterward coinciding with the trade liberalization of the Mexican economy. Using spatial econometric, tools the authors analyze how the process of convergence/divergence has mapped spatially and whether it makes sense to talk about spatial regions in Mexico. Although the rich North-poor South dichotomy has dominated this phenomenon, interesting patterns emerge. Namely the distribution of growth after Mexico's post-liberalization seems to be much less associated with distance to the United States than the authors had initially expected.